ANALISIS METODE BAHTSUL MASAIL MATERI FIQIH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SANTRI - Aziz, Rifki Abdul; Syarifah, Laili; Rohmat, Ali; Abdul Aziz, Rifki (Wahana Islamika, 2025)
This qualitative field research aims to analyze the implementation of Bahtsul Masail activities related to Fiqih material at the Roudlotut Thullab Boarding School and determine its role in enhancing the santri's critical thinking skills, alongside identifying the inhibiting factors to its execution. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, presentation, and conclusion drawing. The results reveal that Bahtsul Masail includes specific components and stages central to the curriculum. The improvement of students' critical thinking skills is evident in their ability to comprehend and articulate problems, identify relevant sources, analyze and link answers to the debated issues, and ultimately determine the most appropriate solution. However, the implementation faces several obstacles, including the low level of santri courage and self-confidence, incomplete reference sources, sub-optimal ability and interest in reading the yellow book, and issues with timely attendance in the forum. The study concludes that Bahtsul Masail is a highly effective method for developing high-level critical thinking in religious education.